2003
DOI: 10.1063/1.1578172
|View full text |Cite
|
Sign up to set email alerts
|

White luminescence from Si+ and C+ ion-implanted SiO2 films

Abstract: The microstructural and optical analysis of SiO 2 layers emitting white luminescence is reported. These structures have been synthesized by sequential Si ϩ and C ϩ ion implantation and high-temperature annealing. Their white emission results from the presence of up to three bands in the photoluminescence ͑PL͒ spectra, covering the whole visible spectral range. The microstructural characterization reveals the presence of a complex multilayer structure: Si nanocrystals are only observed outside the main C-implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 35 publications
0
32
0
Order By: Relevance
“…The opening of the gap of silicon due to quantum confinement has allowed to observe photoluminescence (PL) in the red-infrared spectral region [6]. The emission energy may vary, depending on one hand on the matrix composition, mostly silicon oxide [7,8], also nitride [9] and oxycarbide [10], on the other hand by the incorporation of other elements in the Si-nc like C [11]. In particular, we have previously shown that the use of alternative nanoparticles with different chemical composition may be a viable method to obtain emission in the visible spectrum, in particular by co-implanting silicon-rich silicon oxide (SRSO) with carbon [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The opening of the gap of silicon due to quantum confinement has allowed to observe photoluminescence (PL) in the red-infrared spectral region [6]. The emission energy may vary, depending on one hand on the matrix composition, mostly silicon oxide [7,8], also nitride [9] and oxycarbide [10], on the other hand by the incorporation of other elements in the Si-nc like C [11]. In particular, we have previously shown that the use of alternative nanoparticles with different chemical composition may be a viable method to obtain emission in the visible spectrum, in particular by co-implanting silicon-rich silicon oxide (SRSO) with carbon [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The emission energy may vary, depending on one hand on the matrix composition, mostly silicon oxide [7,8], also nitride [9] and oxycarbide [10], on the other hand by the incorporation of other elements in the Si-nc like C [11]. In particular, we have previously shown that the use of alternative nanoparticles with different chemical composition may be a viable method to obtain emission in the visible spectrum, in particular by co-implanting silicon-rich silicon oxide (SRSO) with carbon [11,12]. In this latter case, the processed structures show a white PL consisting in different bands: one in the red-infrared region attributed to the Si-nc, and two other bands, located in the blue or the green, assigned to the formation of SiC compounds or C graphitic-like aggregates, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon based light sources have been widely investigated for their implementation in integrated photonic circuits [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Cu [1], Ge [2, 3], Si [4,5], or C [6] ions implanted into amorphous SiO 2 (a-SiO 2 ) could be used in the synthesis of ultra fine clusters that can show unique electrical and optical properties. In recent years, swift heavy ion irradiations have also been used to investigate the modification of silicon-based materials, and various phenomena such as swift heavy ion irradiations induced blue-violet photoluminescence (PL) [7][8][9] and new chemical bonds formations [10] in C-doped a-SiO 2 were reported. However, data on micro-structure modifications and the relationships between the PL properties and new structures is still scarce.…”
mentioning
confidence: 99%